Meristem identity and phyllotaxis in inflorescence development - Bartlett, Madelaine E.; Thompson, Beth (Frontiers in Plant Science, 2014)
Inflorescence morphology is incredibly diverse. This diversity of form has been a fruitful source of inquiry for plant morphologists for more than a century. Work in the grasses (Poaceae), the tomato family (Solanaceae), and Arabidopsis (Brassicaceae) has led to a richer understanding of the molecular genetics underlying this diversity. The character of individual meristems, a combination of the number (determinacy) and nature (identity) of the products a meristem produces, is key in the development of plant form. A framework that describes inflorescence development in terms of shifting meristem identities has emerged and garnered empirical support in a number of model systems. We discuss this framework and highlight one important aspect of meristem identity that is often considered in isolation, phyllotaxis. Phyllotaxis refers to the arrangement of lateral organs around a central axis. The development and evolution of phyllotaxis in the inflorescence remains underexplored, but recent work analyzing early inflorescence development in the grasses identified an evolutionary shift in primary branch phyllotaxis in the Pooideae. We discuss the evidence for an intimate connection between meristem identity and phyllotaxis in both the inflorescence and vegetative shoot, and touch on what is known about the establishment of phyllotactic patterns in the meristem. Localized auxin maxima are instrumental in determining the position of lateral primordia. Upstream factors that regulate the position of these maxima remain unclear, and how phyllotactic patterns change over the course of a plant’s lifetime and evolutionary time, is largely unknown. A more complete understanding of the molecular underpinnings of phyllotaxis and architectural diversity in inflorescences will require capitalizing on the extensive resources available in existing genetic systems, and developing new model systems that more fully represent the diversity of plant morphology.